PEMBIMBINGAN NILAI-NILAI AGAMA MELALUI METODE PEMBIASAAN DAN LATIHAN DENGAN PROGRAM SHALAT ZUHUR BERJAMA’AH DI SDN 10 CUBADAK AIR KOTA PARIAMAN - Irfansyah; Kustati, Martin; Gusmirawati; Amelia, Rezki (Cahaya Ilmu Bangsa Institute, 2025)
Education is an important actor to ensure the survival of the nation and can even make each learner's personality have a good character as expected in the educational goals. This mentoring aims to form students' Islamic character values through the method of habituation and training with the zuhur prayer program in congregation. This mentoring method uses the PAR (Participary Action Research) method, an approach whose process aims at learning to solve problems and fulfill the practical needs of the community, as well as the production of science. The stages of this mentoring start from investigating the habits of students in praying together after school. The habituation of zhuhur prayer in congregation begins with guidance on how to do wudhu' properly and correctly, then the sound of the call to prayer and iqamah for students who have been appointed, reading the intention of prayer simultaneously, performing zhuhur prayer in congregation properly and correctly and ending with remembrance and prayer together. The results of mentoring that with the assistance of zuhur prayer in congregation can improve the religious values of students and foster an attitude of responsibility, care and understand the meaning of Islamic religious science in depth to carry out the obligation of zuhur prayer at school to God Almighty. In addition, in this mentoring, the results obtained that the participants were able to carry out the zuhur prayer.